2013
DOI: 10.1007/s00784-013-1130-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different radiopacifying agents on the radiopacity, compressive strength, setting time, and porosity of Portland cement

Abstract: ZrO2 and YbF3 may be used as a suitable alternative to replace Bi2O3 in MTA without influencing its physical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 32 publications
2
34
0
7
Order By: Relevance
“…Camilleri et al [14] found that the hydration of PC with the addition of 30 % ZrO 2 resulted in an increase in pH, calcium ion release, and bioactive potential. Antonijevic et al [15] found that ZrO 2 could be used as a substitute for Bi 2 O 3 in MTA, because this radiopacifier does not alter the physical properties of MTA. Moreover, according to Liu et al [11], the use of ZrO 2 in nanoparticle form in bone cements has demonstrated bioactivity and cytocompatibility.…”
Section: Introductionmentioning
confidence: 98%
“…Camilleri et al [14] found that the hydration of PC with the addition of 30 % ZrO 2 resulted in an increase in pH, calcium ion release, and bioactive potential. Antonijevic et al [15] found that ZrO 2 could be used as a substitute for Bi 2 O 3 in MTA, because this radiopacifier does not alter the physical properties of MTA. Moreover, according to Liu et al [11], the use of ZrO 2 in nanoparticle form in bone cements has demonstrated bioactivity and cytocompatibility.…”
Section: Introductionmentioning
confidence: 98%
“…However, MTA contains bismuth oxide, which is a factor that must be taken into consideration when using this cement as a root-end filling material. Bismuth oxide is added to MTA for radiopacity, but in the long term it can cause changes in the cement, resulting in increased porosity and decreased mechanical resistance 14,15,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The absence of additives may affect the mechanical strength of the material 13 . Also, bismuth oxide is added to MTA for radiopacity, but it can result in increased porosity and decreased resistance in the long term 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, este radiopacificador pode interferir negativamente na porosidade e na resistência à compressão do cimento Portland 21 .…”
Section: Introductionunclassified